Mathematical programming for industrial engineers - Avriel, M.; Golany, B. (Industrial engineering, 1996)
"Bridging the gap between the theory of mathematical programming and the varied, real-world practices of industrial engineers, this state-of-the-art reference/text introduces the latest developments in linear, integer, multiobjective, stochastic, network, and dynamic programming, and details many relevant industrial-engineering applications." "Organized by mathematical-programming categories, Mathematical Programming for Industrial Engineers provides numerous exercises that reinforce essential concepts...examines newly emerging uses for mathematical programming in operations research and management science...compares the formulation, implementation, and success of various mathematical-programming approaches to different planning and control situations...presents practical guidelines for using nonlinear programming software...describes several case studies in full...surveys a range of proven heuristic methods for solving industrial-engineering problems...and more."--BOOK JACKET.